The stability analysis of new power generation based on Ostrowski's theorem. Issue 5 (January 2021) - Yang, Lei; Huang, Wei; Zhang, Dan; Li, Shengnan; Xiang, Chuan; Xi, Xinze; He, Xin
Abstract: The parameter mismatch between the source side and the grid side of the grid-connected system of new energy generation is one of the factors affecting the stable operation of the grid connected system. In order to ensure the safe and stable operation of the system, the stability region of system parameters is worth studying. In this paper, a fast estimation method of stable region of impedance parameters for grid connected inverters is proposed. Firstly, the impedance model of grid-connected system in dq coordinate system is established based on the impedance analysis method, and the return matrix which is the main element influencing the stability is analyzed and deduced. Secondly, the bands containing eigenvalue loci of the return matrix are obtained based on Ostrowski's theorem, and the stability of the system is judged by Nyquist stability criterion. Finally, the simulation results show that the proposed method can quickly estimate the stable region of the impedance parameters of the grid-connected inverter, which verifies the correctness of the method.